The Impact of Macronutrients on Retinal Microvasculature among Singapore Pregnant Women during the Mid-Late Gestation. - Ling-Jun Li; Peng Guan Ong; Marjorelee T Colega; Chad Yixian Han; Ling Wei Chen; Ryan Man Eyn Kidd; Ecosse Lamoureux; Peter Gluckman; Kenneth Kwek; Yap Seng Chong; Seang Mei Saw; Keith M Godfrey; et al. (PLoS ONE)
Background Imbalanced macronutrient intakes can induce impairment of endothelial and vascular function, and further lead to metabolic and cardiovascular disease. However, little is known about the influence of such diets on endothelial and vascular dysfunction in pregnant women, even though high-fat diet is a known risk for pregnancy complications such as gestational diabetes and pre-eclampsia. Objective We aimed to assess the association between maternal macronutrient intakes (protein, fat and carbohydrates), dietary quality and retinal microvascular changes in a multi-ethnic Asian mother-offspring cohort. Methods Pregnant women (n = 614) with singleton pregnancies were recruited during their first trimester from June 2009 to Sep 2010. Maternal diet quality and macronutrient intakes, expressed as a percentage of total energy during pregnancy, were ascertained using 24 hr recalls and 3 d food diaries at 26-28 weeks gestation. Retinal examination was completed at the same clinic visit. Dietary quality was assessed and scored using the Health Eating Index in Asian Pregnant women (HEI-AP), while macronutrients intakes ware expressed as percentages of total energy and further log transformed for analysis. Associations were examined cross-sectionally by substitution models with the use of multiple linear regression. Results In adjusted model, each 20 points decrease in HEI-AP score was associated with a significant increase of 1.70 μm (p<0.05) in retinal venular calibre. Each 0.1 log increase in percentage of total fat intake was associated with a significant increment of 1.84 μm (p<0.05) in retinal venular caliber. Additionally, each 0.1 log increase in percentage of mono-unsaturated fat intake was associated with an increment of 1.84 μm (p<0.01) in retinal venular caliber. Conclusions In this cross-sectional study, we found that women with higher fat and lower protein intakes, and lower diet quality tended to have wider retinal venular caliber, which is suggestive of suboptimal microvasculature.